A problem and its answer - Mačys, Juozas Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2015)
In the article attention is given to the fact that knowing of a partial or complete answer to a math problem can be a big help in solving it. The subject is illustrated by solving some math contest problems.